2021
DOI: 10.3390/v13122383
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting ACSL1-Related Ferroptosis Restrains Murine Coronavirus Infection

Abstract: Murine hepatitis virus strain A59 (MHV-A59) was shown to induce pyroptosis, apoptosis, and necroptosis of infected cells, especially in the murine macrophages. However, whether ferroptosis, a recently identified form of lytic cell death, was involved in the pathogenicity of MHV-A59 is unknown. We utilized murine macrophages and a C57BL/6 mice intranasal infection model to address this. In primary macrophages, the ferroptosis inhibitor inhibited viral propagation, inflammatory cytokines released, and cell syncy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Beatty et al 49 recently reported that ACSL1 promotes conjugated linoleic acids incorporation into neutral lipids, leading to ferroptosis by increasing lipid peroxidation. Another study has shown that triacsin C inhibits ACSL1 to prevent ferroptosis and protects mice from MHV‐A59 infection 50 . Here, it was demonstrated that both GSK3368715 treatment and PRMT1‐knockout induced ACSL1 messenger RNA and protein expression in two AML cell lines.…”
Section: Discussionmentioning
confidence: 67%
“…Beatty et al 49 recently reported that ACSL1 promotes conjugated linoleic acids incorporation into neutral lipids, leading to ferroptosis by increasing lipid peroxidation. Another study has shown that triacsin C inhibits ACSL1 to prevent ferroptosis and protects mice from MHV‐A59 infection 50 . Here, it was demonstrated that both GSK3368715 treatment and PRMT1‐knockout induced ACSL1 messenger RNA and protein expression in two AML cell lines.…”
Section: Discussionmentioning
confidence: 67%
“…Epstein-Barr virus dynamically sensitizes B cells to ferroptosis for latency ( 56 ). In addition, a number of human enteroviruses and coronaviruses induce ferroptosis via acyl-coenzyme A (CoA) synthetase long-chain family member 4 (ACSL4) ( 57 ), and murine coronavirus can trigger ferroptosis through ACSL1 ( 58 ). Moreover, oxidative stress and lipid peroxidation leading to exacerbated inflammation and tissue damage have been considered important in the pathogenesis of different viruses ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of RCD occasionally share the same upstream molecules; accordingly, crosstalk between RCD pathways is inevitable. Ferroptosis is an iron-dependent form of RCD, and differs from apoptosis by excessive lipid peroxidation, lack of glutathione, and inactivation of caspase-3 (50,51). However, a recent study demonstrated that the ER stress-mediated CHOP-PUMA pathway was associated with the interaction between apoptosis and ferroptosis (52).…”
Section: Discussionmentioning
confidence: 99%